Elites’ Social Networks and Politics in the Han Empire (202 B.C.E.–220 C.E.) - Yunxin Li (Journal of Open Humanities Data)
Social networks were heavily intertwined with elites’ social status and political power throughout the Han dynasty. This article introduces the Han Elites’ Social Network Dataset, an open-access dataset that the author collected primarily through manual labor. It contains data on Han elites’ marriage, kinship, patron-client, teacher-disciple, friendship, and recommender-nominee relationships. The article then visualizes and analyzes these social networks in relation to Han politics. It argues that social networks provided individuals with channels for upward social mobility and access to political careers, and that the reliance on different types of networks contributed to the formation of political cliques as well as the growing conflict between the inner court and the outer court.